Intercultural Communication in the Construction of Islamic Teaching - Fajar Wajdu (Palakka : Media and Islamic Communication, 2021)
Communication is understood as a process of interaction between two or more individuals exchanging information using symbols so there is a mutual understanding between them. Every communication phenomenon requires a relationship between individuals or more who exchange information with the aim of conveying a message so each of the involved parties can understand each other. Thus, intercultural dialogue refers to a fact of communication in which participants with different cultural backgrounds are involved in a contact with one another, either directly or indirectly. The teachings of Islam as a religion that loves peace also recognize the existence of cultural diversity as a necessary thing. So Islam teaches its people to always build deep interactions (lita'arafu) between different cultural elements. It is, a dialogical attitude, an attitude of openness to build communication to all cultural elements that surround it. Nation, tribe and ethnicity, beside to religion, is one of the cultural elements that confirms the identity of human groups. These three cultural elements make people feel as part of a certain group and at the same time it makes them feel different from certain groups. Surah al-Hujurat verse 13 acknowledges human diversity. Even though we are both Adam's children and grandchildren, born from the same ancestor, we are aware that we are different both as a nation, ethnicity, race, and as part of a certain religion. Humans by nature always attach their identity to certain groups of people because of the similarity of characteristics. For example, the similarity of language, tribe, race, ethnicity, religion, history and residence. For this reason, the surah al-Hujurat verse 13 recognizes cultural diversity. As humans are culturally diverse, humans must know each other (li taarafu) or build a dialogical attitude on the top of the diversity that surrounds them.